The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0075627
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Maternal and Neonatal Serum Trace Element Concentrations with Neonatal Birth Weight

Abstract: BackgroundTrace elements play important nutritional roles in neonates. Our objective was to examine whether there are differences in maternal/neonatal serum trace element concentrations between mature infants and premature infants.MethodsDuring 2012, 44 infants born at National Center for Global Health and Medicine, Tokyo, Japan, were enrolled. Serum samples were collected to measure serum iron, zinc, copper, and selenium concentrations 5 days after birth. Maternal serum samples were obtained before delivery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
3
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 12 publications
(12 reference statements)
3
28
3
3
Order By: Relevance
“…Of studies that collected both maternal blood at birth and cord blood, one study found only maternal blood levels of Cu was associated with gestational age of the baby, 122 while the other three studies did not find any relationship between birth outcomes and serum Cu levels in either maternal or cord blood samples. 114,118,124 Other studies that used either cord blood, 78 or maternal urine 95 did not find an association between levels of Cu and adverse pregnancy outcomes.…”
Section: Effects Of Environmental Exposures On Fetal and Childhoodmentioning
confidence: 95%
See 2 more Smart Citations
“…Of studies that collected both maternal blood at birth and cord blood, one study found only maternal blood levels of Cu was associated with gestational age of the baby, 122 while the other three studies did not find any relationship between birth outcomes and serum Cu levels in either maternal or cord blood samples. 114,118,124 Other studies that used either cord blood, 78 or maternal urine 95 did not find an association between levels of Cu and adverse pregnancy outcomes.…”
Section: Effects Of Environmental Exposures On Fetal and Childhoodmentioning
confidence: 95%
“…One study from Japan with both maternal and cord blood reported that maternal blood levels of Se at birth were significantly associated with birth weight while cord blood levels of Se were not. 124 …”
Section: Effects Of Environmental Exposures On Fetal and Childhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to Pb was found to be associated with birth weight either negatively [37,38], or insignificantly [34][35][36]. Non-significant correlations have been observed for Hg in maternal blood [35,36,39].…”
Section: Introductionmentioning
confidence: 92%
“…These are required for a variety of biological processes including carbohydrate and protein metabolism, DNA and RNA synthesis, cellular replication and differentiation, and hormone regulation [7,8,9,10]. The importance of zinc to the growth of the fetus is demonstrated by the active transport of zinc across the placenta into the fetal circulation resulting in higher cord blood concentrations compared to those in the maternal circulation [11,12,13,14]. Rodent models of severe maternal zinc deficiency show increased rates of fetal loss and congenital malformations in the surviving fetuses [15] as well as reduced fetal growth [16,17,18], lower implantation rates and impaired placental growth [19], all highlighting the teratogenic effects of zinc deficiency in pregnancy.…”
Section: Introductionmentioning
confidence: 99%